Two new species of Cerapus (Crustacea: Amphipoda: Ischyroceridae) from the Northwest Atlantic and Gulf of Mexico - Drumm, David T. (Zootaxa, 2018)
Examination of material from the Northwest Atlantic and Gulf of Mexico revealed the presence of two new species of the amphipod genus Cerapus. One of the species occurs in the NW Atlantic (Delaware Bay and Great South Bay, New York) and the other species occurs in the Gulf of Mexico (Manatee River, Florida and Corpus Christie Bay, Texas). They can be distinguished from congeners by a combination of characters: number of antennular flagella articles, position of the male gnathopod 2 carpal process, shape of the inner ramus of pleopod 2, presence of a distoventral hook on the uropod 1 peduncle of the male, and the nature of the pereopod 7 spination/setation. They can be distinguished from each other by the number of antennular flagella articles in the female and in overall body size.